The Impact of the COVID-19 Pandemic on Health, Quality of Life and Intrafamilial Relations – A Population-Based Survey in Germany - Klein, Stephanie; Fegert, Jörg M.; Geprägs, Alina; Brähler, Elmar; Clemens, Vera (Frontiers in Psychology, 2022)
The occurrence of the novel severe acute respiratory syndrome coronavirus-2 (COVID-19) at the end of 2019 comes along with many challenges. Besides worry for one’s own health and the well-being of the family, all measures applied to limit the spread of the coronavirus affected daily life. School closures, economic shutdown and contact restrictions have led to high levels of stress. The impact on health and families has been widely discussed. However, population-based data are scarce. Here, we have assessed health, quality of life and intrafamilial relations depending on the COVID-19 pandemic. Using a three-step random-route approach, a population-based sample of 2,515 persons (52.6% female, average age of 50.3 years) was recruited during the second COVID-19 wave in Germany in winter 2020/21. While the majority of participants reported no change in their health status and the relationship with their partner and children, more than half of participants reported a decreased quality of life since the beginning of the pandemic. Female gender, age above 60 years, a low household income, not living with a partner and the experience of childhood adversity were associated with a higher risk for a worsening of health, quality of life and intrafamilial relations. These had already been well-established risk factors ahead of the pandemic. In order to avoid further increase of inequality in our society and more devastating impact of the pandemic on health and intrafamilial relations, low-level support and intervention programs are urgently needed.